Design and Implementation of Computing-based Air Conditioner (AC) (ComBAC) – A Preliminary Work - Ahmad, Afandi; Nizar, Muhammad Shafiq; Mohd Nadzri, Muhammad Muzakkir; Roslan, Muhammad Faris; Amira, Abbes (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Computing-based air conditioner (ComBAC) highlights the concept of spot cooling that helps to reduce energy consumption without sacrificing consumer comfortability, while the conventional air conditioner (AC) cooling down the entire space regardless of occupancy. In this study, National Instruments (NI) myRIO has been explored as a hardware solution, and the advantage of graphical-based programming in LabVIEW has been fully used to design the graphical user interface (GUI) as well as for data acquisition programming. For the input, web camera C170 is used to detect the presence of human/object in a room, while the value of current is being measured using current sensor and later being analysed by NI myRIO to exhibit the energy consumed of an AC. NI myRIO also acts to control the AC, to divert the air flow according to the spot cooling concept and visualisation of energy consumed available via liquid crystal display (LCD). To evaluate the proposed system, ComBAC has been prototyped into a wallmounted AC unit with 2.5 meter height within a 3  3 square meter room floor area. An evaluation for objects/humans detection and dynamic tracking mechanism has been conducted and results obtained shown promising results. The proposed system has successfully captured the presence of object/human in a room, analyse the data and finally portray the value of energy consumption of the AC.